Práticas de integração família-escola como preditoras do desempenho escolar de alunos do 5º ano do ensino fundamental - Colli, Daniel Rodriguez (2016)
The current study sought to evaluate the effect of family-school integration practices on mathematics and Portuguese learning abilities of 5th grade students. It was also measured how changes in family cultural capital could interfere in this relationship. The data used came from the 2011 Saeb microdata, containing information from 3,238,506 students from 128,653 classes of 64,812 schools. The sample included students from federal, state, municipal and private schools from all regions of Brazil. The level of proficiency acquired by students in mathematics and Portuguese calculated by Saeb was used to create the dependent variable. Answers to the Saeb 2011 questionnaires from students, teachers and school principals were used to create the independent variables, which sought to represent issues related to familyschool integration practices. The family-school integration practices represented by these variables were: homework, teacher-parent meetings, school expectations towards the family and school communication strategies to reach families. A multiple regression model was used in order to capture how the independent variables could jointly explain the proficiency of students. Two multiple regression models were created: one having as dependent variable the proficiency in mathematics of the students and the other having as dependent variable the proficiency in Portuguese of the students. Results from the regressions observed that students whose parents or guardians encouraged them to study, read or go to school, were expected to have higher proficiency in mathematics and Portuguese than students whose parents or guardians did not encourage them in these actions. Regarding teacher-parent meetings, it was observed that students, whose parents used to attend to these meetings with high frequency, were expected to have greater proficiency than students whose parents did not attend to the meetings with such frequency. However, when the school used teacher-parent meetings to draw individual attention of parents, students studying in schools using this strategy were expected to have lower proficiency in mathematics and Portuguese than students who were studying in schools that did not believe in this strategy. The communication strategy towards the family that appeared to have the greatest impact on student’s proficiency in mathematics and Portuguese, was calling parents to the school to have a private meeting. Regarding homework, it was observed that, regardless of the cultural capital of the family, students that did homework with high frequency were expected to have higher proficiency in mathematics and Portuguese than students who were not used to doing with such frequency. However, having parents that did not know how to read and write, led students who did homework with high frequency level to improve only one third of the improvement achieved from students that also did homework with high frequency level but had parents that did know how to read and write